THE SPECIFIC CHARACTERISTICS OF PEOPLES AND NATIONS FIGHTING FOR THEIR INDEPENDENCE AS SUBJECTS OF INTERNATIONAL LAW - Ro'zikulova Feruza (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article provides practical information about the concept of subjects of international law and their types. It also discusses the specific characteristics, history, and current role of peoples and nations fighting for their independence as subjects of international law. Analytical views on the place and role of these states in the international arena are presented using current political processes. In the current era of globalization, each state has its own legal system and operates independently internationally. International relations cannot be imagined without subjects of international law. When analyzing subjects of international law, first of all, let us consider what subjects of international law are. They are “subjects that have rights and obligations arising from international law, protect it, and enter into international relations regulated by international law.” Until the 20th century, when the development of international law for many years was a process dependent on states, states were considered the main subjects in international law. It was precisely until this period that states were considered the only subjects of decisive importance in international relations. Historically, states have been the main and primary subjects in international law. There are many theories about subjects of international law. For example, we will study three general theories about subjects of international law. These are: 1- Realistic theory 2- Fantastic theory 3- Functional theory